ANALISA PENERAPAN GREEN MARKETING PADA CITRA PRODUK HAPIHOME AIR PURIFYING BAGS (KANTONG PEMBERSIH UDARA HAPIHOME) - Permatasari, Imas; Bari, Andriansyah (MOTIVASI, 2024)
Purpose– The objective of this research is to examine how green marketing influences the brand perception of Hapihome, a locally produced item specializing in Air Purifying Bags composed entirely of Activated Bamboo Charcoal. These bags have the capability to effectively absorb odors, moisture, and bacteria from the surrounding air. Design/methodology– Utilizing a purposeful sampling approach, the study involved 100 participants and employed Google Forms questionnaires as a data collection method. The analysis of green marketing focused on four key elements: green products, green pricing, green distribution channels, and green promotion. Descriptive analysis, employing frequency tables, was utilized to scrutinize respondent characteristics, while quantitative analysis was conducted using StatisticaI Product and Service SoIutions (SPSS). Findings- The green marketing variables examined in the study exert a notable impact on the brand perception of Hapihome. Green product has the highest influence on the brand image of Hapihome. Consumers tend to choose Hapihome products because they have a brand image associated with environmentally responsible business concepts. The consistency between the promotion carried out and the actual business practices is crucial, as inconsistency can damage the brand image and consumer trust.